(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s ((3HZOGO s)
(3ChdgG (B:s
(3hHYO, aEfg deG cGfJ ebGUO cdGe GdYQH Ydi GNJdGa Ufhag eHfjkG CcKQgG Ydi eYGfj MQhag s
(3BNQgG (B:s
(3hEfeG CgedJ PcQgG gfGc dTgQJgG hZQGHI Gdbhd HMQajJgG hGdcdGe YdjgG ehVY gh Cdjb Hg ef gPG GdcJGH, hGddg Gdehab, ced cJGH s
(3fSNI SGHYI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3cJHJ Yf fSNI SbjeIs
(3hHChdgG agQS ddehVhYGJs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdfMhs